Analisis Efisiensi Biaya Antara Metode Patch Repair (Tambalan) dan Overlay (Pelapisan Ulang) Untuk Perbaikan Jalan Aspal di Banda Aceh - Uskur Reza; Ariansyah, Dedek; Pramanda, Heru; Bunyamin, Bunyamin; Idroes, Imransyah (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2025)
Roads as an element of national transportation have an important role, especially in supporting the economic, social, cultural, and environmental sectors. Road conditions in Banda Aceh in 2025 indicate challenges in infrastructure. In road damage, there are several repairs such as repairs and overlays that require high costs. The purpose of this study is to compare the cost efficiency between the patch repair method and the overlay method. This research method is quantitative with research procedures guided by Bina Marga. Data analysis was carried out in this study using Microsoft Excel. Based on the results of the research that has been done, the level of road damage on Jl. Kamboja with a research sample of 6000 m2, there are 3 types of damage: patches, cracks, and holes. The total amount of damage on this is 30.0 with additional asphalt concrete damage of 0.51% with a damage area of ​​30.8 m2. From the research that has been done, there are 2 repair methods on this road. For road repairs using the patch repair method on Jl. Cambodia spent less time on the project, with a total budget of Rp59,003,177. Patch repairs were more effective and more economical than overlay repairs. Overlay repairs, on the other hand, cost Rp119,633,072.70, taking longer to complete. For emergency budgets, patch repairs are recommended over overlay repairs.